2021
DOI: 10.3390/healthcare9121720
|View full text |Cite
|
Sign up to set email alerts
|

Association between Teenage Pregnancy and Family Factors: An Analysis of the Philippine National Demographic and Health Survey 2017

Abstract: Adolescence is a key developmental period in one’s life course; health-related behaviors of adolescents can be linked to lifelong consequences, which affect their future health. Previous studies highlight the role of family and its significant association with adolescents’ health. In East Asia and the Pacific, the Philippines is the only country that is showing an upward trend of teenage pregnancy while other countries in the region have declining teenage pregnancy rates. Against this backdrop, this study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This is contrary to what has been reported in literature. (Tabei K et al, 2021). In our study, it is possible that the small families were those where adolescents were "married" with one child, making it a small household.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This is contrary to what has been reported in literature. (Tabei K et al, 2021). In our study, it is possible that the small families were those where adolescents were "married" with one child, making it a small household.…”
Section: Discussionmentioning
confidence: 85%
“…This was a surprising nding. However, a recent study indicated the same nding (Tabei K et al, 2021) It indicates that knowledge alone is not enough to prevent pregnancy among adolescents. It is also possible that they acquired the knowledge after getting pregnant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Living with neither parent was found as a risk factor for teenage pregnancy. Furthermore, we found that several sociodemographic factors exhibited a non-uniform increment and reduction in the risk of teenage pregnancy (Tabei et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 78%
“…In addition to policy issues, socio-demographic factors were also found to contribute to the burden of adolescent pregnancy in the country [17,18]. Teenage girls with higher educational attainment and women from wealthier households were found to be less likely to be pregnant than women with lower educational attainment and women from poorer households [17][18][19]. In addition, contraceptive use was found to be associated with adolescent pregnancy, but is more likely due to improper use and/or usage after pregnancy [18].…”
Section: Introductionmentioning
confidence: 99%